The poet's mind the psychology of Victorian poetry 1830-1870 - Tate, Gregory, 1983- (Oxford : Oxford University Press, 2013)
'The Poet's Mind' is a comprehensive study of the ways in which Victorian poets thought and wrote about the human mind. It argues that these poets used their writing both to express psychological processes of thought and feeling and to subject those processes to scrutiny and analysis.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: English poetry -- 19th century -- History and criticism; Psychology in literature; Thought and thinking in literature